The School Retention Project far Mother and Pregnant Students. A socio-educational project that challenges the school dropout prediction in the Buenos Aires southern area (Praxis Educativa, 2023)
This article develops the School Retention Program for Mothers and Pregnant Students beginnings that hasbeen operating in the City of Buenos Aires (Argentina) since 1999. Following a qualitative approach and onthe basis of case studies, we problematize the Program origins asan oriented policy in the Buenos Airessouthern area and analyze the pedagogical devices created to guarantee the educational continuity of thisparticular population.
Keywords: pregnancy and maternity in adolescence; education policies; right to education; gender